Anti-Endothelial Cell Antibodies are not frequently elevated in hospitalized patients with COVID-19 - Henry, Brandon; Benoit, Stefanie; Vikse, Jens; Favaloro, Emmanuel; Benoit, Justin; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
n/a